Hybrid carbon fibre architectures for high performance, high volume applications - Evans, Anthony David (2018)
The interest in compression moulded discontinuous carbon fibre compounds is growing for semi-structural automotive applications, with target Takt times of less than 5 minutes. The main advantage of these compounds, such as sheet moulding compounds (SMC), is that they produce complex 3D geometries by using in-mould flow during compression. This results in short cycle times by eliminating preforming and infusion stages, generating low wastage by using net-weight charges and keeping costs low by minimising touch labour.